Odraz višestupanjskog modela karcinogeneze na incidenciju raka u ljudskoj populaciji - primjer raka debelog crijeva : doktorska disertacija - Božikov, Jadranka (J. Božikov, 1997)
Summary: The main ideas of multistage theory of carcinogenesis are outlined and models of carcinogenesis as, well as their applications are referenced and reviewed starting from the 1950-s up to the most recent results. Age-periodcohort models are also described as an example of statistical models. The features of mathematical and simulation models are described and methods and techniques for their design and solving used in present work are emphasised. The epidemiology of colorectal cancer is presented with particular consideration of two hereditary conditions: adenomatous polyposis coli (FAP) and hereditary non-polyposis colorectal cancer (HNPCC). The characteristic of these two syndromes are listed together with their genetic background.